Conclusion (Scottish Historical and Archaeological Internet Reports, 2011)
The Neolithic timber hall is only the fourth to be excavated in Scotland while the Bronze Age cemetery is notable for the high-status artefacts recovered. The Anglian hall provides clear evidence of Northumbrian settlement in SW Scotland away from important monastic sites, which previously had been largely inferred from historical records, Anglian place-names and the discovery of Anglian crosses and other sculpture.